INOVASI PENGEMBANGAN BUMBU KARI PASTA DAN BUBUK DENGAN CITARASA ASAP MENGGUNAKAN ASAP CAIR DAN TEPUNG ASAP - , RAHMI, Prof. Dr. Ir. E. Purnama Darmadji, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Desire for smoked flavor that maintain in this modern age which usually emerge by cooking process with charcoal or ebony then hit on idea to do innovation. In this research, specific smoke flavor engineering be able to innovate by adding liquid smoke or smoke powder into one of kind Indonesia cuisine, i.e. curry. The aims of this research to obtain proper formulation of adding liquid smoke and smoke powder into paste and powder curry seasoning, so produce that instant seasoning product of curry in package with smoke flavor. Formulations of addition liquid smoke into paste curry seasoning in this research are 0,04%, 0,24%, 044%, 0,64%, and 0,84%, but percentage formulations of addition smoke powder into powder curry seasoning are 0,22%, 0,42%, 0,62%, 0,82%, and 1,02%. Furthermore, the organoleptic test includes preference test and discription test on the odor, the taste, and overall the smoke flavor. The results of preference test showed that the optimal formulation of liquid smoke addition into instant paste curry seasoning is 0,24%, with water content 24,23%